Geopolitical Ramifications of Cybersecurity Threats: State Responses and International Cooperations in the Digital Warfare Era - Aisha Adeyeri; Hossein Abroshan (Information)
As the digital environment progresses, the complexities of cyber threats also advance, encompassing both hostile cyberattacks and sophisticated cyber espionage. In the face of these difficulties, cooperative endeavours between state and non-state actors have attracted considerable interest as crucial elements in improving global cyber resilience. This study examines cybersecurity governance’s evolving dynamics, specifically exploring non-state actors’ roles and their effects on global security. This highlights the increasing dangers presented by supply chain attacks, advanced persistent threats, ransomware, and vulnerabilities on the Internet of Things. Furthermore, it explores how non-state actors, such as terrorist organisations and armed groups, increasingly utilise cyberspace for strategic objectives. This issue can pose a challenge to conventional state-focused approaches to security management. Moreover, the research examines the crucial influence of informal governance processes on forming international cybersecurity regulations. The study emphasises the need for increased cooperation between governmental and non-governmental entities to create robust and flexible cybersecurity measures. This statement urges policymakers, security experts, and researchers to thoroughly examine the complex relationship between geopolitics, informal governance systems, and growing cyber threats to strengthen global digital resilience.